The applicability of analytical-band Monte Carlo for modelling high field electron transport in GaAs - Choo, K Y; Ong, D S (2004)
An analytical-band Monte Carlo model incorporating four non-parabolic spherical valleys to represent the first two conduction bands has been developed to model hot electron transport and impact ionization in GaAs. We have tested the performance of this simple model against full-band Monte Carlo simulations for calculating the probability distribution function of impact ionization path length, time and energy; and transient velocity overshoot at high fields. This simpler model is: found capable of reproducing the full-band model results satisfactorily but at much lower computational cost.